Economic Inertia and Economic Growth: Is There Any Contradiction?; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Afonasova M. A. Margarita (2017, 2017)
Title screen